Visit from Purdue University, USA. - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
Prof. Dr. Ragu, Purdue University, met our officials on 11th April 2016 during his courtesy visit.